The effect of the inhomogeneous microstructure and texture on the mechanical properties of AZ31 Mg alloys processed by friction stir processing - Peng, Jinhua (2020)
Friction stir processing caused obvious grain refinement and texture modification for the experimental AZ31 magnesium alloy. The microstructure, texture as well as mechanical properties were tested for samples cut at different depths from the processed surface of the work-pieces. The micro-hardness in the stir zone was improved to varying extent at different depth. The top layer showed the highest value due to the high density of dislocations. The tensile properties were improved significantly due to the microstructure and texture modification. The texture was weakened in the stir zone, which led to a lower yielding strength and a higher elongation due to the easier activation for basal slip. The true stress-strain curves could be divided into five stages depending on different strain hardening mechanisms, including twinning and dislocation slip. Conventional Hollomon equation was used to describe dislocation related plastic deformation stage while a corrected Arrhenius equation was successfully applied to describe twinning dominated stage.